Field experiments testing for apparent competition between primary parasitoids mediated by secondary parasitoids - Morris, R; Muller, C; Godfray, H (2001)
1. Two field manipulation experiments were performed to look for apparent competition between primary parasitoids of aphids, mediated by shared secondary parasitoids. In each case the frequency of secondary parasitism on a 'focal' species was compared in the presence or absence of a 'treatment' species and its aphid host. 2. In both experiments the focal species was Aphidius ervi (Haliday) attacking Acyrthosiphon pisum (Harris) (pea aphid). In the first experiment the treatment species was Aphidius rhopalosiphi (De Stefani-Perez) attacking Sitobion avenae (Fabricius) (a grass aphid) and in the second Aphidius microlophii (Pennachio and Tremblay) attacking Microlophium carnosum (Buckton) (nettle aphid). 3. No significant effects of either the presence of A. rhopalosiphi or of its host on secondary parasitism of A. ervi were detected in the first experiment. 4. In the second experiment, rates of secondary parasitism were estimated twice: a significant effect of treatment was found on the first occasion but not the second. In the former, parasitism was highest in the presence of the treatment species and its host, intermediate when just the host was present, and lowest when both were absent. 5. We discuss the evidence for apparent competition in host-parasitoid communities.